Well you want (x - 4y = -4) to equal (y=mxb)
You need to get y alone in the first equation, and solve from there.
x - 4y = -4 [here's the equation]
-x . . . . - x [subtract x on both sides]
-4y = -4 - x [you get this]
/-4 . . /-4 [divide both sides by -4 to get y alone]
y = 1 - x
(y = 1 - x) can be
(y = 1 + -x) or (y = -x + 1)
I don't know what your m or b is, so just plug in the y and x that you found, and no problem.
2007-01-29 12:03:59
·
answer #1
·
answered by T.VO 3
·
0⤊
0⤋
y=mx+b?
bring the 'x' to the opposite side of the 'y' so you will get:
-4y = -x - 4
now we need to divide everything by -4 to get:
y = (1/4)*x + 1
so now we have a line that slopes from the bottom left to the top right...remember, rise over run. Our slope is 'm', or in this case, one-fourth...so that means it goes up one, and over four.
The y-intercept is 'b' of course, so that means our line crosses the y-axis at 1.
Hope that helps, have a nice day. Good luck.
2007-01-29 19:58:49
·
answer #2
·
answered by sealguy77 2
·
0⤊
0⤋
you must write the equation in the form
y=mx+n where m is the slope and n the intercept
x-4y=-4 so 4y= x+4 and y = 1/4*x +1
2007-01-29 19:57:15
·
answer #3
·
answered by santmann2002 7
·
0⤊
0⤋
You need to solve the equation for the variable y:
x - 4y = -4
Subtract x from both sides :
x - 4y -x = -4 -x
-4y = -4 -x
Now divide both sides by -4 :
y = (-4)/(-4) - (x)/(-4)
y = 1 + x/4
or
y = x/4 + 1
So,
m = 1/4 (slope) and b = 1 (y-intercept)
2007-01-29 19:59:46
·
answer #4
·
answered by sabseg50 1
·
0⤊
0⤋
You want to solve for y, so multiply the entire equation by -1/4. This will give you an equation with y having a coefficient of +1. Next step is to subtract x from both sides of the equation; this will eliminate the x from the left (placing it on the right) leaving the y alone. Which is what you wanted.
2007-01-29 19:57:09
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
This is simple...hold on a sec. ..
To make x-4y= -4 into y=mx+b form you need to do the following :
Move the x to the opposite side by subtracting (since its a possitive originally) :
x-4y= -4
-x -x
---------------
-4y= -x - 4
Now divide by -4 on everything (since you want to get the 'y' alone) :
-4y/4= -x/4 - 4/4
Total :
y= -1/4x - 1
~ ~ K.N.~ ~ Hope that helped you . !! :-)
2007-01-29 19:54:23
·
answer #6
·
answered by Kathy© 4
·
0⤊
1⤋
ok move x to the other side
-4y=-x-4
divide by -4
y=1/4x+1
2007-01-29 19:56:12
·
answer #7
·
answered by MS32291 4
·
0⤊
0⤋
1). Subtract x on both sides. Cancel like terms.
2).Divide by -4 on both sides
2007-01-29 19:55:40
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
x - 4y = -4
x = 4y - 4
4y = x + 4
y = x/4 + 1
2007-01-29 19:57:01
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
Add -x to both sides and they divide everything by -4.
2007-01-29 19:54:25
·
answer #10
·
answered by alwaysmoose 7
·
0⤊
0⤋